Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.34172/ijhpm.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Missed Nursing Care in Nursing Homes: A Multicentre Cross-sectional Study

Abstract: Background: Despite its association with patient safety, few studies on missed nursing care have been conducted in nursing homes. We aimed to describe individual and environmental factors in a sample of registered nurses (RNs) reporting missed nursing care in nursing homes, and to explore the association between these factors and missed nursing care. Methods: In the present, multicentre cross-sectional study, 217 RNs from 43 nursing homes in Northern Italy reported all episodes of missed nursing care (ie, any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Healthcare systems should maintain, and be prepared to implement, plans for pandemic events, and hospital managers should draw up specific emergency plans that define the human resources required in case of a long-term pandemic with recurrent waves, based on competencies, skill mix (e.g., of experienced and novice nurses), and job rotations. Nurse staffing should be proportionate to the clinical complexity of patients and to the organizational complexities to individualize care, minimizing the risk of missed care and patient death [38]. These actions would improve the healthcare system's response and alleviate the stress imposed by crises, although maintaining the highest standard of nursing care delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare systems should maintain, and be prepared to implement, plans for pandemic events, and hospital managers should draw up specific emergency plans that define the human resources required in case of a long-term pandemic with recurrent waves, based on competencies, skill mix (e.g., of experienced and novice nurses), and job rotations. Nurse staffing should be proportionate to the clinical complexity of patients and to the organizational complexities to individualize care, minimizing the risk of missed care and patient death [38]. These actions would improve the healthcare system's response and alleviate the stress imposed by crises, although maintaining the highest standard of nursing care delivered.…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on the fact that neglect, as defined by researchers, is common in Norwegian nursing homes [4]. Prior research presents a numerous examples of and causal explanations for neglect happening in nursing homes based on the outsiders' perspectives on this phenomenon [14,[35][36][37][38][39][40][41]. We add to this knowledge by studying the meaning making efforts of the nursing home staff.…”
Section: Discussionmentioning
confidence: 99%
“…Hence findings from acute care may not be generalizable to nursing homes [9]. Campagna, et al (2022) on the other hand, concluded that missed care in hospital environments are relevant for nursing homes due to similarities such as patients with severe and complex clinical conditions, high perceived workload, and less qualified staff [41].…”
Section: Introductionmentioning
confidence: 99%
“…As such, nurses may take these aspects for granted and thus not report them (Coffey et al, 2019). It is also possible that chronic understaffing, compounded by the pandemic, forced NH nurses to focus on more practical issues when communicating (Campagna et al, 2021). This issue deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%